2023
DOI: 10.3390/biomedinformatics3040066
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Mosaic of Therapeutic Potential: A Scoping Review of Neural Network Applications in Psychotherapy Enhancements

Alexandre Hudon,
Maxine Aird,
Noémie La Haye-Caty

Abstract: Background: Psychotherapy is a component of the therapeutic options accessible in mental health. Along with psychotherapy techniques and indications, there is a body of studies on what are known as psychotherapy’s common factors. However, up to 40% of patients do not respond to therapy. Artificial intelligence approaches are hoped to enhance this and with the growing body of evidence of the use of neural networks (NNs) in other areas of medicine, this domain is lacking in the field of psychotherapy. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Scoping reviews are considered a valid approach when systematic reviews and metaanalyses are unable to meet the necessary objectives or the needs of knowledge users. A scoping review conducted by Alexandre Hudson and coworkers [18] focused on the use of neural networks in the context of psychotherapeutic approaches. From the eight studies reviewed, three main uses were identified: prediction of therapeutic outcomes, content analysis, and automated categorization of psychotherapeutic interactions.…”
Section: Statistical Synthesis Of Results From a Series Of Studiesmentioning
confidence: 99%
“…Scoping reviews are considered a valid approach when systematic reviews and metaanalyses are unable to meet the necessary objectives or the needs of knowledge users. A scoping review conducted by Alexandre Hudson and coworkers [18] focused on the use of neural networks in the context of psychotherapeutic approaches. From the eight studies reviewed, three main uses were identified: prediction of therapeutic outcomes, content analysis, and automated categorization of psychotherapeutic interactions.…”
Section: Statistical Synthesis Of Results From a Series Of Studiesmentioning
confidence: 99%